Penciptaan Naskah Drama Ambu Hawuk Berdasarkan Tradisi Lisan dan Perspektif Jender - Budi Darma (Resital: Jurnal Seni Pertunjukan (Journal of Performing Arts), 2011)
Artikel ini membahas proses penciptaan naskah drama Ambu Hawuk . Naskah ini diadaptasi dari cerita lisandan mitologi lokal yang berkembang di daerah Sunda. Cerita lisan dikumpulkan melalui wawancara mendalamdengan para informan yang mewakili berbagai versi. Setidaknya terdapat enam versi tradisi lisan mengenai tokohini, yaitu versi Cikawungading, Manonjaya, Cianjur, Sukaraja, Parungponteng, dan Galunggung. Dari keenamversi tersebut terdapat variasi dan kesamaan. Naskah ini mencoba membangkitkan kembali semangat feminismedalam peristiwa-peristiwa yang dijalin dalam legenda Ambu Hawuk. Sistem patriarki masyarakat Sunda lebih seringmemandang perempuan sebagai sebuah kaum yang memiliki keterbatasan dibandingkan dengan kaum laki-laki.Cerita ini menggambarkan seorang perempuan yang dianggap berada di belakang laki-laki dan menjadi bayangbayangseorang laki-laki, muncul menjadi seorang pemimpin.Kata kunci: Ambu Hawuk, naskah drama, tradisi lisan.ABSTRACTThe Creating Process of Drama Script Ambu Hawuk Based on the Oral Tradition and the GenderPerspective. This article discusses about the creating process of the drama script Ambu Hawuk. This script was adaptedfrom the oral story and the local mythology developed in Sunda. This oral story was compiled through the intensive interviewwith some sources of information that represented many kinds of versions. There are six versions of the oral traditiontalking about this character, namely: the version of Cikawungading, Manonjaya, Cianjur, Sukaraja, Parungponteng, and Galunggung. Of those six versions, there are varieties and similarities. This script tries to develop feminism spirit on someinterrelated events in Ambu Hawuk legend. From the perspective of Sundanese’ point of view on the patriarchy system, women are regarded as God’s creature who have more basic physical and mental limitations than men. This story describes a woman who is regarded as a person behind the man’s existence and becomes the man’s shadow; but soon afterwards, she becomes a leader.Keywords: Ambu Hawuk, Drama Script, Oral Tradition